RADIATION HYGIENIC CONSEQUENCES OF THE ACCIDENT AT THE CHERNOBYL NPP AND THE TASKS OF THEIR MINIMIZATION - G. G. Onischenko (Радиационная гигиена, 2016)
The paper presents data on the role and results of activities of Rospotrebnadzor bodies and institutions in the field of ensuring population radiation protection during various periods since accident at the Chernobyl NPP. Radiation hygienic characterization of territories affected by radioactive contamination from the accident, population exposure dose range, issues of ensuring radiological well-being of population and ways of their solution are being presented in the paper.